Measuring the Impact of Clean Energy Production on CO2 Abatement in Denmark: Upper Bound Estimation and Forecasting. (1st November 2020) - Christensen, Bent Jesper; Datta Gupta, Nabanita; Santucci de Magistris, Paolo
Abstract: Using annual data from 1978 through 2016, and monthly data from January 2005 through November 2017 from Denmark, we provide a precise estimate of the upper bound on the potential impact of the adoption of wind energy on the reduction of CO 2 emissions from energy production. We separate causal impacts from endogenous effects in regressions using instrumental variables including average wind speed, and from spurious effects in dynamic systems using impulse-response analysis and cointegration techniques. A one percentage point increase in the share of wind in total energy production is found to cause a reduction in CO 2 emissions of the order 0.3%, based on endogeneity-corrected regression, and 0.5% over 2 years in a fractional vector error-correction model, after allowing the cumulative effects to take place. This corresponds to an upper bound estimate of 0.69 tonnes of CO 2 emissions avoided per additional MWh of wind energy produced. We find that after a structural break at the time of introduction of the EU ETS and the Kyoto Protocol in 2005, the country has been on track towards meeting its long-term goals for emission reduction and green energy production, but not before.